2022
DOI: 10.3389/fendo.2022.969149
|View full text |Cite
|
Sign up to set email alerts
|

Scores of peripheral neuropathic pain predicting long-term mortality in patients with type 2 diabetes: A retrospective cohort study

Abstract: ObjectivesDiabetic peripheral neuropathic pain (DPNP) is a prevalent chronic complication in patients with diabetes. Using a questionnaire is helpful for DPNP screening in outpatients. In this retrospective cohort, we aimed to examine whether DPNP diagnosed based on scoring questionnaires could predict long-term mortality in outpatients with type 2 diabetes.MethodsWe enrolled 2318 patients who had joined the diabetes pay-for-performance program and completed the annual assessments, including both the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(86 reference statements)
0
1
0
3
Order By: Relevance
“…Within our cohort of Vietnamese factory workers, the prevalence of neuropathic pain was estimated to be 1%, which is low compared to estimates of global prevalence ( 10 ). Specifically, some previous studies reported that the prevalence of neuropathic pain in Canada was 17.9% ( 23 ), Brazil was 10% ( 24 ), French was 6.9% ( 25 ), the UK was 8% ( 26 ), Australia was 3.3% ( 11 , 23 , 27 ), Brazil ( 24 ), was 10%, Thailand was 24.0% ( 28 ), and Taiwan was 7.9% ( 29 ). This figure may have been underestimated due to various external factors.…”
Section: Discussionmentioning
confidence: 99%
“…Within our cohort of Vietnamese factory workers, the prevalence of neuropathic pain was estimated to be 1%, which is low compared to estimates of global prevalence ( 10 ). Specifically, some previous studies reported that the prevalence of neuropathic pain in Canada was 17.9% ( 23 ), Brazil was 10% ( 24 ), French was 6.9% ( 25 ), the UK was 8% ( 26 ), Australia was 3.3% ( 11 , 23 , 27 ), Brazil ( 24 ), was 10%, Thailand was 24.0% ( 28 ), and Taiwan was 7.9% ( 29 ). This figure may have been underestimated due to various external factors.…”
Section: Discussionmentioning
confidence: 99%
“…Diyabetik periferik nöropati, diyabetin en sık görülen uzun vadeli komplikasyonlarından biridir 2 ve tip 2 DM tanısı alan hastalarda diyabetle ilişkili mortalite için bağımsız bir belirteçtir. 3 İntraepidermal sinir liflerinin (IENF) ölçümü, küçük lif nöropatisinin mevcut altın standart ölçüsüdür. 13 Ancak bu, cilt biyopsisi gerektiren minimal invaziv bir prosedürdür.…”
Section: Discussionunclassified
“…1 Diyabetik periferik nöropati (DPN), DM'li hastaların en az %50'sini etkileyen, diyabetin en sık görülen uzun vadeli komplikasyonlarından biridir ve tip 2 diyabet tanısı alan hastalarda diyabetle ilişkili mortalite için bağımsız bir belirteçtir. 2,3 Başlangıçta küçük miyelinsiz C liflerini etkileyen duyusal kayıp ve ağrı, ardından büyük, miyelinli sinir lifi tutulumu ile karakterizedir. Diyabetik nöropati esas olarak periferik sinir duyarlılığının kaybı ile ilişkilidir.…”
Section: Introductionunclassified
“…Він складається з двох блоків запитань: перший блок складається із 7 запитань до хворого, за допомогою яких виявляють сенсорні симптоми, а саме спонтанний біль, до якого відносяться такі симптоми, як: відчуття печії, болюче відчуття холоду, відчуття, як від ударів струмом, та наявність парестезії і дизестезії: відчуття повзання мурашок, поколювання, оніміння, свербіж; до другого блоку опитувальника входять 3 висновки лікаря на підставі клінічного огляду, що дає можливість лікарю виявити алодинію та негативні сенсорні симптоми. Якщо позитивних відповідей понад 4 із 10 пунктів, то це свідчить про наявність у пацієнта невропатичного болю [8,12].…”
Section: наука -практиці охорони здоров'яunclassified